Valid and valuable: lower attaining pupils' contributions to mixed attainment mathematics in primary schools. Issue 2 (4th May 2021) - Barclay, Nancy
ABSTRACT: Existing research establishes that lower attaining pupils derive mathematical learning benefit from working in mixed attainment groupings. However, gains for lower attaining pupils are seen to derive from the contributions of higher attaining peers; evidence of the contributions that lower attaining pupils make to mixed attainment activity is currently lacking. This study contributes evidence of the merits of mixed attainment working through its focus on the mathematical contributions of lower attaining primary pupils to mixed attainment pair activity. It draws on the construct of mathematical noticing and focuses on the development of pupils' noticing of mathematical pattern, structure and property. Close video analysis of pupils' speech and action during paired activity establishes that primary school mixed attainment working can produce bi-directional benefits, with lower attaining pupils making important contributions to task progress and contributing mathematical insights in advance of and beyond those of their higher attaining partners.